Emission of volatile sulphur compounds during swine manure composting: Source identification, odour mitigation and assessment. (November 2022) - Gao, Xingzu; Yang, Feiyu; Cheng, Jingwen; Xu, Zhicheng; Zang, Bing; Li, Guoxue; Xie, Xiaomin; Luo, Wenhai
Graphical abstract: Highlights: Organic and inorganic sulphur substances led to VSCs in swine manure composting. COS, CS2, MeSH and Me2 SS were mainly derived from cysteine and methionine. Me2 S and EtSH were dominated by the reduction of sulphite and sulphate. Fe2 O3 reduced VSC emission by 46.7–80.9% during composting. Fe2 O3 weakened odour intensity, olfactory value and non-carcinogenic risk of. VSCs. Abstract: This study aimed to identify the sources of volatile sulphur compounds (VSCs) and evaluate their mitigation by ferric oxide (Fe2 O3 ) during swine manure composting. Four chemicals, including l -cysteine, l -methionine, sodium sulphite, and sodium sulphate, were further added to simulate organic and inorganic sulphur-containing substances in swine manure to track VSC sources during composting. Results show that sulphur simulants induced the emission of six common VSCs, including methyl sulphide (Me2 S), dimethyl sulphide (Me2 SS), carbonyl sulphide (COS), carbon disulphide (CS2 ), methyl mercaptan (MeSH), and ethyl mercaptan (EtSH), during swine manure composting. Of them, COS, CS2, MeSH and Me2 SS were predominantly contributed by the biodegradation of methionine and cysteine, while Me2 S and EtSH were dominated by the reduction of sulphite and sulphate. Further Fe2 O3 addition at 1.5 % of total wet weight of composting materials immobilized elemental sulphur and inhibited sulphate reduction to reduce the emission of VSCs by 46.7–80.9 %. Furthermore, odour assessment indicated that adding Fe2 O3 into composting piles significantly reduced the odour intensity level to below 4, the odour value of VSCs by 47.1–81.3 %, and thus the non-carcinogenic risk by 68.4 %.